A Comparative Clinical Study to Evaluate the Effect of Arohana Krama and Sadharana Krama Matra Basti with Vajigandhadi Taila in the Management of Gridhrasi (AYUSHDHARA, 2022)
Gridhrasi is a Rujapradhana Nanatmaja Vata Vyadhi, intervening with the functional ability of low back & lower limbs. Low back pain is the major cause of morbidity throughout the world affecting mainly the young adults. Life time incidence of low back pain is said to be 50-70% with the incidence of Sciatica more than 40%. Among various Ayurvedic treatments of Gridhrasi; Basti is a unique procedure which eliminates the aggravated Doshas from the body as such it was described Ardhachikitsa of all treatment. In present study effort is made to compare the effect of Arohana Krama and Sadharana Krama Matra Basti with Vajigandhadi Taila in the management of Gridhrasi. Minimum 40 patients who fulfilled the inclusion criteria, randomly distributed into 2 groups of 20 patients each. When both the groups were compared clinically for Ruk, Toda, Stamba, Spandana & SLR test, Both the groups show statistically significant effect with p